Stylizing the Mundane: Bernice Morgan’s Random Passage - Whalen, Tracy (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2001)
This article offers a detailed critical reading of Bernice Morgan’s Random Passage, a novel about nineteenth century Newfoundland. It focuses particularly on the book’s lexical and grammatical choices, and explores how novelistic style functions rhetorically to construct an aesthetic of the mundane. The author then considers how a novel, especially one that performs a style of the mundane, can be thought of as liminoid festival space and how it might encourage communitas or a shared reading that “bring[s] about a temporary reconciliation among conflicting members of a single community” (Turner 1982:21). She argues that the novel, finally, can be read through the communal eyes of tourist desire, a stance that ultimately replicates, rather than subverts, existing attitudes towards place, particularly nostalgic understandings of history. A shared understanding of Newfoundland as a leisure space, as a tourist space, affects how readers, both local and non-local, read and value Random Passage. The author argues that particularly at a time of depopulation, unemployment, and resource depletion, a style of the mundane — one achieved through lexical choice, grammar, and narrative organisation in the novel — constitutes a persuasive means of celebrating the province together.